ANALISIS KRIPTOGRAFI MENGGUNAKAN ALGORITMA VIGENERE CIPHER DENGAN MODE OPERASI CIPHER BLOCK CHAINING (CBC) - Nurnawati, Erna Kumalasari (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
Data security’s problem is the important thing in organization or personal area. Moreever, if the data in network and connecting through public network, such as internet. The data have to protected by unregistered user, to protect from either data damaged or lossed. The aim of this research is how to secure the data, and security of sending mes-sage from the unregistered user. Criptography using Vigenere Chipher algorithm were adapted Cipher Block Cha-ining (CBC) mode operation is the one of security methods. These application though da-ta encription and decription using Borland Delphi 6.0 and the file extention of result is .enc. Combining Vigenere Cipher and CBC mode operation will produce new methode named Vigenere Cipher+ that repair the disadvanrages of Vigenere Cipher.